Unravelling the rationalities of childhood cycling promotion. (June 2022) - Silonsaari, Jonne; Simula, Mikko; Te Brömmelstroet, Marco; Kokko, Sami
Highlights: The study problematises instrumental and functional rationalities of cycling promotion. Different representations of 'children' as 'cyclists' are analysed. Results highlight how childhood mobilities emerge through social and institutional relations. Abstract: Decrease of children's independent mobility (CIM) has worried academics, policymakers, educators and other professionals for decades. Research and policy often emphasise that promoting children's physically active and independent transport modes as cycling is important to achieve better public health, solve environmental challenges and increase related economic benefits. Yet, cycling promotion is not a neutral process and all promotion efforts are derived from latent notions of 'cyclists' and 'cycling'. This paper discusses different rationalities of childhood cycling promotion and the representations of 'children' as independent 'cyclists' they entail. We argue that in order to efficiently promote cycling across contexts, we should better understand children's cycling experiences and meanings they ascribe to it and how their mobilities emergence in the flux of social, institutional and political relations. By applying action research to a local cycling promotion project in Finland we explore how instrumental, functional and alternative rationalities emerged and resulted in differing representations of children as cyclists. While all rationalities played a role in different stages of the project, the results highlight that alternative rationalities as children's autonomy, positive emotions and friendships were considered the most important drivers of new cycling practices among project participants. In conclusion we propose children's autonomous mobility as the most appropriate term to depict their cycling and other self-imposed (but relational) mobility practices.